PENAFSIRAN HAKIM MENGENAI KETENTUAN PENJATUHAN PIDANA MINIMUM KHUSUS TERHADAP ANAK YANG BERKONFLIK DENGAN HUKUM DALAM TINDAK PIDANA KESUSILAAN - , dian nur pratiwi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research is aimed at analyzing the implementation of the of specific minimum criminal provisions in criminal cases against decency committed by children, analyzing basis of judgesâ considerations in making decision related criminal cases against decency committed by children that contains specific minimum criminal sanctions, and reviewing the interpretation used by Judges in order to seek legal interpretation on the cases of children who commit crime against decency which includes specific minimum criminal provisions. This research is an empirical normative research using primary data, i.e. interviews, and secondary data consisting of primary legal, secondary and tertiary materials. Methods and instruments of data collection included documentation and documentary study which were supported with interviews. Data of literature materials were analyzed qualitatively. Results of research and discussion indicated that there were two different views in judicial practice of the implementation of criminal sanctions against children as perpetrators of crime against decency on children that contains the specific minimum criminal provisions, namely Judges passed a decision in accordance with the special minimum criminal provisions and Judges passed a decision criminal under the special minimum criminal provisions. There were 2 bases of judgesâ consideration in imposing criminal penalty to children, namely juridical consideration, drawing facts revealed in the trial, and non-juridical consideration, including consideration on the basis of Moral Justice and Social Justice, and principle of justice, principle of utility, and the principle of legal certainty for the sake of the children. The interpretation used by the Judges in two (2) decisions examined in this research, namely Decision No. 10/Pid.Sus/2013/PN.P.Bun was systematic interpretation and futuristic interpretation, while the interpretation of Judges in Decision No. 164/Pid.Sus/2013/PN.Mkd was grammatical interpretation.